2017
DOI: 10.2147/ndt.s143234
|View full text |Cite
|
Sign up to set email alerts
|

Children with borderline intellectual functioning and autism spectrum disorder: developmental trajectories from 4 to 11 years of age

Abstract: BackgroundStudies on autism have tended to focus either on those with intellectual disability (ie, those with intellectual quotient [IQ] under 70) or on the group that is referred to as “high-functioning”, that is, those with borderline, average or above average IQ. The literature on cognition and daily functioning in autism spectrum disorder combined specifically with borderline intellectual functioning (IQ 70–84) is limited.MethodsFrom a representative group of 208 preschool children diagnosed with autism sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 28 publications
0
0
0
Order By: Relevance
“…Barnevik Olsson et al [ 46 ] reported that children with both BIF and ASD experience several developmental and neuropsychiatric problems. These include attention deficits, difficulties with regulating activity levels, impulsivity, speech and language problems, and behavioral problems.…”
Section: Comorbid Disordersmentioning
confidence: 99%
“…Barnevik Olsson et al [ 46 ] reported that children with both BIF and ASD experience several developmental and neuropsychiatric problems. These include attention deficits, difficulties with regulating activity levels, impulsivity, speech and language problems, and behavioral problems.…”
Section: Comorbid Disordersmentioning
confidence: 99%